(untitled) (Journal of Medicine, 2008)
Surgery does not mean operation only. It is the total evaluation of the patient along with the appropriate and comprehensive management of the specific surgical condition altogether make the surgery an âArt’. As surgeons we are immensely privileged that we are being trusted by people who often have no previous knowledge of us to make decisions on their behalf, carry out necessary measures or action, where someway or other slight lack of vigilance or any negligence at any step in the total process of management may result in various morbidities and might even cost their life. This, on the other hand, imposes a huge responsibility upon the surgeons and that every surgeon must be very vigilant in his all and every step which starts pre-operatively and continues over the subsequent whole management process till the smooth and uneventful post-operative recovery period. It includes, establishment of a normal (or at least near normal) homeostatic status and it’s maintenance is highly desirable in the whole peri-operative period. To assess the preoperative volumaeic status of the patient accurately and to replace any existing fluid or electrolyte deficiency as well as any other ongoing losses during the intra or per-operative as well as during the postoperative period, if any, it’s proper and appropriate replacement or correction is of fundamental importance for every successful surgery. Â DOI = 10.3329/jom.v9i1.1427 J MEDICINE 2008; 9 : 50-57